Eco-Efficiency and Waste Management in Small-Scale Enterprises: Cost Efficiency and Environmental Management Roles - Girindratama, Muhammad Wisnu (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2026)
This study was grounded in the growing importance of sustainable business practices among small-scale enterprises (SSEs), particularly in addressing environmental challenges through eco-efficiency. It aims to examine the effect of eco-efficiency on waste management in SSEs, with cost efficiency and environmental management as mediating factors. Additional analyses also assess whether these factors moderate the relationship between eco-efficiency and waste management. Drawing on the resource-based view (RBV), this study positions eco-efficiency as a strategic mechanism. A quantitative approach was employed using survey data collected from 101 SSEs and analyzed with PLS-SEM. The results showed that eco-efficiency does not directly translate into improved waste management. Instead, it strengthens cost efficiency and environmental management as internal capabilities that support waste management. Environmental management, as a higher-order capability, directly improves waste management by embedding sustainability into business operations. Cost efficiency, although important for resource optimization, does not directly influence waste management, indicating that financial efficiency alone was insufficient to drive sustainable waste practices. Further analysis showed that only environmental management mediates the eco-efficiency–waste management relationship, while only cost efficiency moderates it. The study suggests that SSE managers should prioritize environmental management systems alongside efficiency-oriented strategies to achieve sustainable waste management outcomes.